Given:
The equation is:
[tex]4x+2xy^2+44=y^3[/tex]
To find:
The equation of the tangent on the given equation at point (-3,2).
Solution:
We have,
[tex]4x+2xy^2+44=y^3[/tex]
Differentiate with respect to x.
[tex]4(1)+2[x(2yy')+y^2(1)]+0=3y^2y'[/tex]
[tex]4+4xyy'+2y^2=3y^2y'[/tex]
[tex]4+2y^2=3y^2y'-4xyy'[/tex]
[tex]4+2y^2=(3y^2-4xy)y'[/tex]
Isolate y'.
[tex]\dfrac{4+2y^2}{3y^2-4xy}=y'[/tex]
Now, we need to find the value of the derivative at point (-3,2).
[tex]y'_{(-3,2)}=\dfrac{4+2(2)^2}{3(2)^2-4(-3)(2)}[/tex]
[tex]y'_{(-3,2)}=\dfrac{4+8}{12+24}[/tex]
[tex]y'_{(-3,2)}=\dfrac{12}{36}[/tex]
[tex]y'_{(-3,2)}=\dfrac{1}{3}[/tex]
It means the slope of the tangent line is [tex]\dfrac{1}{3}[/tex].
The equation of tangent line that passes through the point (-3,2) with slope [tex]\dfrac{1}{3}[/tex] is:
[tex]y-y_1=m(x-x_1)[/tex]
[tex]y-2=\dfrac{1}{3}(x-(-3))[/tex]
[tex]y-2=\dfrac{1}{3}x+1[/tex]
[tex]y=\dfrac{1}{3}x+1+2[/tex]
[tex]y=\dfrac{1}{3}x+3[/tex]
Therefore, the equation of tangent line is [tex]y=\dfrac{1}{3}x+3[/tex].